Public policies and the Digital Gender Gap: analysis in Costa Rica (2020-2022) - Martinez Toledo, Yanet (2023)
Introduction: This research incorporates the intersectional perspective to make visible the diversity of gender identities, sexual orientation, age, class, geographic location; as key elements for overcoming the Digital Gender Divide in public policies on gender and Information and Communication Technologies. Objective: To analyze how gender and the Digital Gender Gap (GDG) are articulated in the design of public policies in order to know: what is the conception of women and their agency? Method: qualitative research that studies national policies and programs, applying categories of intersectional analysis articulated to gender. Results: Through the analysis, the conceptions and views on women reproduced in public policies were identified. In addition, of the routes proposed to reduce the DGD. There is an understanding that DGD is part of a complex system of inequalities based on gender inequality and the reproduction of gender roles and its impact on the barriers to access, use and appropriation of ICTs.